The role of asthma's basic therapy in the development of endothelial dysfunction in children - Veronika M. Dudnyk; Katerina V. Khromykh (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2015)
Purpose - estimation of basic anti-inflammatory therapy with inhaled glucocorticoids in the development of endothelial dysfunction in children with asthma. Materials and methods. Comprehensively examined 224 children with asthma, aged 6 - 17 years, with determination of homocysteine and vascular endothelial growth factor. 40 healthy children were examined as a control group. Results. Established that the likelihood of adverse effects when using the highest GCI monotherapy (OR 8,889; 95% CI 4,803 - 16,449) and combination therapy with mast cell membranes stabilizeres (OR 1,111; 95% CI1,051 - 2,734). Determined that the risk factors increase homocysteine than 17.36 (11.3 - 24.5) mmol / l and VEGF above 431.66 (238.04 - 658.09) pg / ml in serum of children with asthma were using of doses aerosol inhalators without conveying device and without increasing of IGC dose.